Native Washerwomen, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2008)
Photo of a group of Creole washerwomen and children by a stream.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Laundresses--Trinidad and Tobago; Rivers--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Laundry--Trinidad and Tobago; Work; Manners and customs--Trinidad and Tobago; Women--Trinidad and Tobago; Girls--Trinidad and Tobago; Children--Trinidad and Tobago